The effect of soil moisture stress on growth and flowering of carnations - Kowalczyk, Richard Adam, author (Colorado State University. Libraries, 1967)
The effect of differences in soil moisture stress, provided by the use of different soils and depths of soil, on yield and quality of carnations was investigated. A technique that would offer a better indication of when to water carnations under greenhouse conditions was also evaluated. The values of bulk density, moisture content at all suctions and total pore space of the best soils were an average of the extremes of all soils compared. Reduction of soil depth from 8 to 4 inches increased problems that result from too much or insufficient water. Yield and grade were best on plants grown in 8-inch soil. Raw field soil had a decreased yield due to an aeration problem when placed in a greenhouse bench. The effect of stress was most noticeable in the flowering of the second crop which was delayed up to 5 weeks under high stress. Indications were that some stress may be essential for production of higher grade carnations. The number of stomatal and epidermal cells per unit area increased as either solar radiation or soil moisture stress increased. Stomata on leaves from plants grown under high stress adapted to the unfavorable growing conditions by having a greater resistance to transpiration. The use of stomatal index was not beneficial in understanding stomatal distribution. A higher correlation was found between transpiration rate and stomatal aperture than transpiration rate and solar radiation. Although the lithium chloride hygrometer was easy to use, it was not sensitive enough to be used in a greenhouse as an indication of when to water. The measurement of stomatal apertures by the use of silicon rubber impressions was too laborious to be used as a practical field technique.
Keywords: Carnations; Growth (Plants); Soil moisture